PENGARUH KOMITMEN ORGANISASI, PENGAWASAN, DAN PEMBERIAN SANKSI TERHADAP DISIPLIN KERJA DAN KINERJA PADA PEGAWAI KANTOR BAPPEDA, DISPORABUDPAR, DISNAKERTRANS,DAN DINAS KESEHATANKABUPATEN INDRAGIRI HILIR - Hariyanto, Hariyanto (Jurnal Tepak Manajemen Bisnis, 2017)
This research was conducted at the Agency Bappeda, Disporabudpar, Disnakertrans and Department of Healt Indragiri Hilir-Riau. This study aimed to analyze the effect caused by Employee Monitoring, Providing Penalties, Work Discipline And Employee Performance. The population of this study were 219 Civil Servants. The sampling technique was conducted using purposive sampling and random sampling and cluster sampling to produce as much as 142 Civil Servants as samples. Technique data analysis is done by Path Analysis using SPSS version 20.00.The final conclusion is that organizational commitment and significant positive effect on employee performance, organizational commitment is not positive and significant impact on employee discipline, then monitoring positive and significant impact on work discipline. Furthermore, providing penalties a significant effect on work discipline, providing penalties positive and significant impact on the performance of employees, work discipline positive and significant impact on employee performance and organizational commitment, supervisory and providing penalties indirect effect on employee performance with the discipline of work as mediating variable.The study recommends to the leadership of the organization either Head or Head of Department is expected to increase the commitment of the organization, supervision and providing penalties because it directly can improve work discipline and better employee performance in the future. The study also recommends that the Head of the Agency or the Head of Department to increase the commitment of the organization, supervision and providing penalties mediated by a good working discipline will improve employee performance indirectly.